SAMPLING MIKROBIOLOGI LIMBAH BIOMEDIS RUMAH SAKIT DI KOTA SEMARANG JAWA TENGAH - Stalis Norma Ethica; Sakti Imam Muchlissin; Ragil Saptaningtyas; Agus Sabdono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The present study aimed to propose a technical strategy of sampling for obtaining microbiological samples from liquid biomedical wastes generated by hospitals in Semarang City, Central Java Province, Indonesia.  The samples will be used to evaluate bioremediation ability of the hydrolytic bacteria isolated from the waste. It was hoped that the proposed strategy could help to guide researchers about appropriate sampling practices on hospital biomedical wastes from IPAL of Indonesian hospitals. As mandated by the Indonesian law, the handling of hospital liquid waste in Indonesia should follow Permenkes No.1204/2004, while the liquid waste standard should meet the Kepmen LH No.58/1995, reaffirmed by Perda Provinsi Jawa Tengah No.10/2004 about liquid waste standard issued by the Governor of Central Java. Based on formal regulations and safety aspects, it is proposed that the strategy for a proper microbiological sampling practice in terms of hospital liquid biomedical waste should include: (1) Permit letter from hospital where sampling location is; (2) Relevant sampling method based on research purpose (3) Standard, anti-leaked, properly labelled sampling containers(4) Proper sampling equipment based on sampling purpose (5) Adequate sampling transport equipment; (6) The use of standard personal protection equipment (PPE); and (7) Vaccine for the sampling workers (hepatitis B vaccination ismandatory).  Keywords: microbiological sampling, hospital biomedical waste, microbial bioremediation, sampling strategy,Indonesian sampling regulation